Microbiota and volatilome of dry-cured pork loins manufactured with paprika and reduced concentration of nitrite and nitrate. (November 2021) - Belloch, Carmela; Neef, Alexander; Salafia, Clarissa; López-Diez, José Javier; Flores, Mónica
Graphical abstract: Highlights: Paprika addition did not impact the physicochemical parameters of dry-cured loins. Paprika affected composition of loin microbiota, free amino acids and VOCs production. Staphylococcus dominated in loins microbiota, but Bacillus co-dominated in paprika loins. Nitrite/nitrate reduction led to an increase of microbial diversity in loins. VOCs derived from microbial activity were more abundant in paprika loins. Abstract: Dry-cured pork loin is a very popular meat product in Mediterranean countries. Pork-loin is manufactured rubbing curing salts, nitrite and nitrate, and spices on the surface of the loin which is then dry-cured or smoked for several months. Although nitrite-derived compounds are crucial for the microbiological safety and development of a distinct flavour, there have been recent concerns about the adverse health effects of nitrite-derived compounds driving to the reduction of curing agents in meat products. In this study, we have evaluated the differences in microbiota and aroma of dry-cured pork loins manufactured with or without paprika and reduced ingoing amounts of nitrate and nitrite. Staphylococcus dominated the microbiota of pork loins without paprika, regardless of the nitrite and nitrate reduction. On the contrary, the reduction of nitrite and nitrate in loins with paprika had an important effect on the microbiota. In these loins a codominance of Staphylococcus and Bacillus together by Enterobacteriaceae occurred. Moreover, paprika addition and reduction of nitrite and nitrate seemed to promote proliferation of lactic acid bacteria. Occurrence of these genera was correlated with the generation of free amino acids and their derived volatile compounds setting clear differences in the aroma profile of dry-cured loins.